Reproduction and adaptation characteristics in D’man sheep - Lahlou-Kassi, A.; Benlamlih, S.; Boukliq, R. (Agricultural and Food Science, 1988)
D’man breed (D) is found in the oasis of the subsaharian regions of Morocco and reared usually in sedentary type of management with small flocks (< 10 ewes). Preliminary field surveys showed that D is early maturing, prolific and aseasonal. Hence, a multidisciplinary research programme on D was started in 1974. This paper reports the findings of these studies and describes the approach used to (1) characterize and evaluate the performances of D in field and station, (2) study the physiological mechanism involved in its peculiar reproduction and production, (3) study the genetic basis of reproduction parameters, and (4) evaluate use of D in crossbreeding schemes to improve the productivity of other Moroccoan breeds. Results show that D is one of the rare breeds that is simultaneously early maturing, highly prolific and completely aseasonal. However, studies on water turnover and nitrogen recycling show that D is not well adapted to hot climate and poor nutrition. Its reproduction parameters are relatively independent of photoperiod and related to a low sensitivity to negative oestrogen feedback. D male is characterized by high libido and can be used for synchronizing oestruses through the »ram effect». Crossbreeding experiments with non-prolific sheep confirm the heritability of reproductive parameters. However, the genetic basis for these is not yet well known.